LEGAL ANALYSIS OF CHILD CUSTODY RIGHTS IN CASES OF DIVORCE - Dikki Saputra Saragih; Rolando Marpaung; Malthus Hutagalung; Seni Fifi Meriani Zalukhu (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Child protection law No. 23 of 2020 article 14, which states that "Every child has the right to be raised by his own parents, unless there are valid reasons and/or legal regulations indicating that the separation is in the best interests of the child and is a consideration final". The aim of this research is to find out how child custody is determined after divorce. To find out what the judge considers in decisions regarding custody of minor children as a result of divorce. This type of research is qualitative descriptive research which aims to describe the characteristics of an individual, the condition of a particular symptom or group or to determine the distribution of a symptom or to determine whether there is a relationship between a symptom and other symptoms in society. Conclusion The determination of child custody as a result of divorce according to Presidential Instruction Number 1 of 1991, for children who are not yet adults or under 12 (twelve) years of age is the mother's right. Meanwhile, for adult children, it is up to the child to choose between his father and mother as the holder of his child's rights.